A Fuzzy ARTMAP Probability Estimator with Relevance Factor - Răzvan Andonie; Lucian Sasu (European Symposium on Artificial Neural Networks Bruges (Belgium), 2023)
An incremental, nonparametric probability estimation procedure using a variation of the Fuzzy ARTMAP (FAM) neural network is introduced. The resulted network, called Fuzzy ARTMAP with Relevance factor (FAMR), uses a relevance factor assigned to each sample pair, proportional to the importance of that pair during the learning phase. We prove that our probability estimator is correct. The FAMR can be used both as a classifier and as a probability estimator.